2019
DOI: 10.1111/jcmm.14134
|View full text |Cite|
|
Sign up to set email alerts
|

SSRP1 promotes colorectal cancer progression and is negatively regulated by miR‐28‐5p

Abstract: In this study, microarray data analysis, real‐time quantitative PCR and immunohistochemistry were used to detect the expression levels of SSRP1 in colorectal cancer (CRC) tissue and in corresponding normal tissue. The association between structure‐specific recognition protein 1 (SSRP1) expression and patient prognosis was examined by Kaplan‐Meier analysis. SSRP1 was knocked down and overexpressed in CRC cell lines, and its effects on proliferation, cell cycling, migration, invasion, cellular energy metabolism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…Hence, targeting N4BP1 or TNIP1 will result in strong activation of NFkB signaling, which in turn boosts MHC-I expression. Indeed microRNA (miR) 28-5p is an inhibitor of N4BP1 and has been demonstrated to act as a tumor suppressor in many cancer types, including colorectal cancer, renal cell carcinoma, and hepatocellular carcinoma [ 65 , 66 , 67 ]. In addition, MiR-1180 and miR-486 have also been demonstrated to induce NFkB activation via targeting of several inhibiting players of the NFkB pathway, including Cezanne, A20, and TNIP1-3 [ 68 , 69 ].…”
Section: Inducing Mhc-i Expression In Cancer Via Nfkb Stabilizatiomentioning
confidence: 99%
“…Hence, targeting N4BP1 or TNIP1 will result in strong activation of NFkB signaling, which in turn boosts MHC-I expression. Indeed microRNA (miR) 28-5p is an inhibitor of N4BP1 and has been demonstrated to act as a tumor suppressor in many cancer types, including colorectal cancer, renal cell carcinoma, and hepatocellular carcinoma [ 65 , 66 , 67 ]. In addition, MiR-1180 and miR-486 have also been demonstrated to induce NFkB activation via targeting of several inhibiting players of the NFkB pathway, including Cezanne, A20, and TNIP1-3 [ 68 , 69 ].…”
Section: Inducing Mhc-i Expression In Cancer Via Nfkb Stabilizatiomentioning
confidence: 99%
“…The second FACT subunit SSRP1-M was initially thought to lack histone binding (185), however it was later shown to bind H3-H4 as well as H2A-H2B (186). In vivo the SSRP1 subunit enhanced xenograft tumor growth/proliferation and SSRP1 overexpression in vitro promoted EMT (187). Mechanistically, miRNA-28-5p was implicated in upstream negative regulation of SSRP1 (187), however given the discovery of PH domains within Spt16 and SUPT16H-H3/H4 binding, it is reasonable to suggest that SSRP1 promotes EMT via epigenetic regulation of key genes, albeit further research is required.…”
Section: Remodeling Our Understanding Of Chromatin Machinery In Emtmentioning
confidence: 99%
“…Moreover, this result was further validated by the luciferase reporter assays. SSRP1 has been considered as an oncogene in a multiple of human malignancies including HCC [16][17][18]. Thus, we asked whether miR-4784 functioned as a tumor suppressor by targeting SSRP1 in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The bioinformatics analysis indicated that SSRP1 mRNA might be a potential target of miR-4784 (Figure 4(a)). Of interest, several studies have showed that SSRP1 acts as an oncogene in multiple malignancies including HCC [16][17][18].…”
Section: Mir-4784 Performs Tumor-suppressive Function By Targeting Ssmentioning
confidence: 99%